A PRAGMATIC ANALYSIS OF THE SPEECH ACTUSED IN PULP FICTION MOVIE SCRIPT - Putra, N.G.P.; Ramendra, D.P.; Suprianti, G.A.P (Language and Education Journal Undiksha, 2018)
Communication is not only applied in real life, but also applied in media literature such as film as a means of entertainment to convey meaning to the audience. The author tries to analyze the use of speech act types; illocutionary act, which is classified by Searle (1980) into 5 types namely representative, directive, commissive, expressive and declarative. And communication strategies as proposed by Mullany (2010), direct speech act and indirect speech act that are used to convey meaning in speaking between the speaker and the interlocutor. Data were analyzed by describing the data submitted by Best and Khan (2008). Research shows that the use of the illocutionary act is more common in the directive act while no data is found in the pronunciation of the declarative act. In conclusion, some sayings have corresponding meanings and indirectly have different meanings.